2014
DOI: 10.1371/journal.pone.0083902
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design of a New Trypanosoma rangeli Trans-Sialidase for Efficient Sialylation of Glycans

Abstract: This paper reports rational engineering of Trypanosoma rangeli sialidase to develop an effective enzyme for a potentially important type of reactivity: production of sialylated prebiotic glycans. The Trypanosoma cruzi trans-sialidase and the homologous T. rangeli sialidase has previously been used to investigate the structural requirements for trans-sialidase activity. We observed that the T. cruzi trans-sialidase has a seven-amino-acid motif (197–203) at the border of the substrate binding cleft. The motif di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(58 citation statements)
references
References 33 publications
1
57
0
Order By: Relevance
“…Using an enzyme engineering approach it was shown that the loop in TctrS promotes transglycosylation, increasing product yield and reducing hydrolysis, effects that were attributed to a perturbation of the water-binding network [154]. Using an enzyme engineering approach it was shown that the loop in TctrS promotes transglycosylation, increasing product yield and reducing hydrolysis, effects that were attributed to a perturbation of the water-binding network [154].…”
Section: Transferring Compared With Hydrolysing Sialidasesmentioning
confidence: 99%
“…Using an enzyme engineering approach it was shown that the loop in TctrS promotes transglycosylation, increasing product yield and reducing hydrolysis, effects that were attributed to a perturbation of the water-binding network [154]. Using an enzyme engineering approach it was shown that the loop in TctrS promotes transglycosylation, increasing product yield and reducing hydrolysis, effects that were attributed to a perturbation of the water-binding network [154].…”
Section: Transferring Compared With Hydrolysing Sialidasesmentioning
confidence: 99%
“…It contained 5.7% (w/w) of covalently linked sialic acid and was used as the donor molecule for enzymatic production of 3 0 -sialyllated-lactose (with lactose as acceptor) using an engineered sialidase, Tr13, from Trypanosoma rangeli reacting for 60 min at 30°C and pH 6.5. The Tr13 enzyme was produced in Pichia pastoris and purified as described previously [2]. The enzyme and cGMP residues were removed from the post reaction mixture by ultrafiltration using a 10 kDa commercially available Alfa Laval RC70PP membrane before the sample was frozen and stored until it was used for filtration experiments.…”
Section: Chemicalsmentioning
confidence: 99%
“…Commercially sustainable processes for production of HMOs are therefore of great interest for both society and the dairy industry. 3 0 -sialyllactose (SL) is an HMO molecule which is currently produced from lactose and casein glyco macro peptide (cGMP) via an enzymatic reaction that relies on the presence of a large excess of lactose [2][3][4]. Once produced, the separation and purification of SL from lactose is a crucial step, as the SL added to the commercial formula should be as pure as possible.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our key idea was to engineer loop structures near the active site with the aim to confer water exclusion during catalysis to enhance transglycosylation. This strategy was recently successfully applied to improve the trans‐sialylation of a sialidase . However, as opposed to the design of the trans‐sialylation loop, for which a native trans‐sialidase structure was available (i.e., the Trypanosoma cruzi trans‐sialidase), there were no immediate real transhexosaminidase template enzymes available for engineering.…”
Section: Introductionmentioning
confidence: 99%